2016
DOI: 10.5603/fm.a2015.0072
|View full text |Cite
|
Sign up to set email alerts
|

A computed tomography study on the correlation between the morphometry of the suprascapular notch and anthropometric measurements of the scapula

Abstract: Background: The suprascapular notch is a clinically important site because it is the main site of injury and compression of the suprascapular nerve. Its shape and (Folia Morphol 2016; 75, 1: 87-92)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
67
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(102 citation statements)
references
References 14 publications
(24 reference statements)
17
67
6
Order By: Relevance
“…The incidence of suprascapular foramen in our study is comparable and in concordance with various ethnic population based studies. After going through available literature of study on completely ossified STSL, we found concordance of our incidence with Polguj M et al [16] (Poland) and Grey DJ et al [17] (America and Europeans) as shown in In our morphological study on 106 scapulae, we found most common type of SCN is type III (40.6%) and this observation is in accordance with previous cited studies by Jadhav S et al [9] (39.79%)and Agrawal D et al [21](45.0%).Second most common finding regarding our study is type I (26.4%) of suprascapular notch variation and this finding is similar with previous studies by Iqbal K et al [7] (22.5%), Kannan U et al [13] (20.0%) and Nagraj S et al [22](23%) . There is lack of standard classification regarding morphological study on SCN of scapula.…”
Section: Discussionsupporting
confidence: 70%
“…The incidence of suprascapular foramen in our study is comparable and in concordance with various ethnic population based studies. After going through available literature of study on completely ossified STSL, we found concordance of our incidence with Polguj M et al [16] (Poland) and Grey DJ et al [17] (America and Europeans) as shown in In our morphological study on 106 scapulae, we found most common type of SCN is type III (40.6%) and this observation is in accordance with previous cited studies by Jadhav S et al [9] (39.79%)and Agrawal D et al [21](45.0%).Second most common finding regarding our study is type I (26.4%) of suprascapular notch variation and this finding is similar with previous studies by Iqbal K et al [7] (22.5%), Kannan U et al [13] (20.0%) and Nagraj S et al [22](23%) . There is lack of standard classification regarding morphological study on SCN of scapula.…”
Section: Discussionsupporting
confidence: 70%
“…The combined average of both sides was 69.09± 4.16mm. Polguj M et al [15] noted the combined GCI to be 72.35±5.55, which was higher than the present study. The mean cavity index of 70.37±4.08% on right side while 68.59±4.36% on left side recorded by Dhindsa et al [16] were found very close to present study.…”
Section: Discussioncontrasting
confidence: 55%
“…Therefore various studies have been done on suprascapular notch variations in different populations. Rengachary et al, [6] Ticker et al, [11], Bayramoglu et al, [12] Natsis et al, [13] Sinkeet [14] Wang [15] and Polguj [16]. Depending on the shape of suprascapular notch and the degree of ossification, Rengachary et al, [6] classified SSN into six types .…”
Section: Resultsmentioning
confidence: 99%